2013
DOI: 10.2337/dc13-0770
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcomes After Noncardiac Surgery in Patients With Diabetes

Abstract: OBJECTIVETo investigate whether diabetes affects perioperative complications or mortality and to gauge its impact on medical expenditures for noncardiac surgeries.RESEARCH DESIGN AND METHODSWith the use of reimbursement claims from the Taiwan National Health Insurance system, we performed a population-based cohort study of patients with and without diabetes undergoing noncardiac surgeries. Outcomes of postoperative complications, mortality, hospital stay, and medical expenditures were compared between patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 37 publications
(55 reference statements)
2
106
1
Order By: Relevance
“…Second, because this study lacks detailed grading of preoperative pressure ulcer [26], we could not investigate the impact of severity of pressure ulcer on postoperative mortality. In addition, as our study used ICD-9-CM codes to define coexisting medical conditions and postoperative complications, miscoding due to human error could not be avoided; however, the accuracy of the National Health Insurance Research Database has been accepted in numerous scientific publications [13][14][15][16]24]. Finally, possibly inadequate adjustment of confounding factors in use of propensity score-matched pair technique might cause neglected bias in the study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, because this study lacks detailed grading of preoperative pressure ulcer [26], we could not investigate the impact of severity of pressure ulcer on postoperative mortality. In addition, as our study used ICD-9-CM codes to define coexisting medical conditions and postoperative complications, miscoding due to human error could not be avoided; however, the accuracy of the National Health Insurance Research Database has been accepted in numerous scientific publications [13][14][15][16]24]. Finally, possibly inadequate adjustment of confounding factors in use of propensity score-matched pair technique might cause neglected bias in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between preoperative pressure ulcer and postoperative adverse outcomes was still unclear, previous studies had identified factors associated with postoperative pressure ulcer such as old age, types of surgeries and coexisting medical conditions [17,18]. These factors were also associated with major adverse events after surgery [14][15][16][19][20][21][22][23][24][25]. To reduce the confounding errors, we adjusted these covariates using propensity score-matched procedure and then controlled these factors in the multivariate Poisson regression models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations